Is the press presenting (neoliberal) foreign residency laws in a depoliticised way? the case of investment visas and the reconfiguring of citizenship - Santos, T. R.; Castro, P.; Guerra, R. (Journal of Social and Political Psychology, 2020)
Neoliberalism calls upon the social sciences to explore how legal innovations – new laws and policies – incorporating neoliberal values are presented to the citizenry. An example are investment visas, a new legal instrument regulating foreign residency. Investment visas reconfigure citizenship by prioritising neoliberal values, by privileging economic capital over labour and over place-and-community involvement in the host country. They also create sub-groups within a same migrant community. The press can present these changes by highlighting how they involve choices among competing values, stimulating debate, or it can hide such choices, offering a depoliticised coverage of the issue. This paper explores how investment visas were presented to the Portuguese public by the press, in connection with the Chinese, its main beneficiary community. The analysis is two-fold: first, a thematic analysis focuses on the representation of the Chinese in two newspapers (n = 525 articles), exploring whether it differentiates the investment visa sub-group within the Chinese community; second, a content analysis examines whether the law’s transformations to citizenship are presented in a depoliticised way (n = 164 articles). Findings indicate that the press shows Chinese investment visa beneficiaries as disconnected from other representations of the Chinese. Additionally, the investment visa laws are presented in a depoliticised way: one (uncontested) perspective is privileged, emphasizing their benefits. Conflicting values are almost absent, and the deterritorialised aspect of citizenship is left unproblematized. We conclude by discussing the implications of this type of coverage in shaping social debate and for the socio-psychological study of legal innovations and of citizenship.